Forced Degradation Studies of Ivabradine and In Silico Toxicology Predictions for Its New Designated Impurities - Pikul, Piotr; Jamrógiewicz, Marzena; Nowakowska, Joanna; Hewelt-Belka, Weronika; Ciura, Krzesimir (Frontiers in Pharmacology, 2016)
All activities should aim to eliminate genotoxic impurities and/or protect the API against degradation. There is a necessity to monitor impurities from all classification groups, hence ivabradine forced degradation studies were performed. Ivabradine was proved to be quite durable active substance, but still new and with insufficient stability data. Increased temperature, acid, base, oxidation reagents and light were found to cause its degradation. Degradation products were determined with the usage of HPLC equipped with Q-TOF-MS detector. Calculations of pharmacological and toxicological properties were performed for six identified degradation products. Target prediction algorithm was applied on the basis of Hyperpolarization-activated cyclic nucleotide-gated cation channels, as well as more general parameters like logP and aqueous solubility. Ames test and five cytochromes activities were calculated for toxicity assessment for selected degradation products. Pharmacological activity of photodegradation product (UV4), which is known as active metabolite, was qualified and identified. Two other degradation compounds (Ox1 and N1), which were formed during degradation process, were found to be pharmacologically active.